Multi scale power spectral density subband gradient-based spectrum sensing algorithm and performance analysis - Yang ZHANG; Hua PENG; Ke-xian GONG (Tongxin xuebao)
In response to the challenge of the complex environment such as non-cooperative communication and wide-band electromagnetic spectrum regulation, where existing missing priori information, serious channel distortion and un-even color noise in frequency domain, a novel spectrum sensing algorithm based on multi-scale power spectral density subband gradient(MPSG)was proposed. The proposed algorithm, not relying on any prior information, calculated gra-dients of sections for the power spectrum and detected the narrowband signals by adaptive double threshold, which im-proved the stability of wideband spectrum sensing through multi-scale technique. Theoretically expressions of statistical properties, false alarm probability, detection probability and decision threshold in different channels were deduced. The theoretical analysis and simulation results prove that the novel algorithm overcomes effectively the color noise with low computational complexity and strong real-time in Gaussian noise and fading channel, which can accomplish occupying band range localization of prime users. In addition, the proposed algorithm is robust for noise varia uncertainty, even in the low SNR environment.